Effect of Thickness on Structural and Optical Properties of CdO Thin Films Prepared by Chemical Spray Pyrolysis Method - Hameed, Sabreen A. (NeuroQuantology, 2020)
Cadmium oxide thin films have been deposited on glass substrates at 400oC by using chemical spray pyrolysis technique show spray time dependence growth when the substrate temperature is constant. Thin films have different thickness of about (200,225,250) nm measured by gravimetric method. The XRD results presented that the nature of the films are polycrystalline with a cubic structure and the preferred orientation is (111). The crystallite size, texture coefficient, number of grains, dislocation density and micro strain were calculated. Field Emission Scanning Electron Microscopy results showed Multiple shapes nano structures as semispherical, plates and rods. The optical properties was studied in (300-900) nm wavelength range. The energy band gap Eg is in the range of (2.3–2.6)eV, the absorption coefficient value is high(α >104 cm-1) and its Suitable for solar cell uses.